P560 HIV preventive behaviour during last sex with a non-steady partner – self-reported data from 113, 000 MSM from 66 countries. (14th July 2019) - Marcus, Ulrich; Schink, Susanne; Schmidt, Axel; Caceres, Carlos; Jonas, Kai; Veras, Maria; Fernández-Davila, Percy; Barros, Henrique; Weatherburn, Peter; Hickson, Ford; Reid, David; Casabona I Barbara, Jordi
Abstract : Background: In Europe and the Americas, men-who-have-sex-with-men (MSM) are heavily affected by HIV. Having traditionally relied mainly on condoms and sero-adaptive behaviours to prevent HIV transmission, more recently biomedical prevention strategies such as pre-exposure prophylaxis (PrEP) among HIV-negative and viral suppression among HIV-diagnosed men have been adopted. We analysed the choice of HIV prevention behaviour (HIV-PB) and determinants of the lack of defined HIV-PB during sex among MSM across 66 countries. Methods: Between October 2017 and May 2018, self-reported data were collected online: EMIS-2017 in 48 European countries (including Lebanon and Israel), and LAMIS in 18 predominantly Latin American countries. Here we focus on men who reported on their last anal sex with a non-steady partner. We used a multilevel multivariate regression model (MMRM) to identify demographic and contextual factors associated with the lack of HIV-PB such as condom use, undetectable viral load, PrEP use or serostatus disclosure. Results: Our analysis included 71, 123 MSM from EMIS-2017 and 41, 834 MSM from LAMIS. Condom use remained the primary HIV-PB, followed by sero-adaptive behaviours. Using antiretrovirals as HIV-PB accounted for 14.9% (HIV-diagnosed men: 83.4%; other MSM: 3.1%). No HIV-PB as defined above was reported by 20.5%, ranging from 12.1 to 39.7% across countries. In the MMRM, increasing age, false assumptions about HIV recognisability, struggling financially, living in smaller settlements, having intercourse in a gay sex venue, a group-sex setting, and receiving money for sex were associated with increased odds for lack of HIV-PB. The strongest associations were observed among those who had never been tested for HIV (OR=1.86, 95%CI: 1.79–1.94) and those who had not bought or received condoms in the last 12 months (OR=2.75; 95%CI: 2.60–2.91). Conclusion: About 1-in-5 MSM did not use HIV-PB. While antiretrovirals for treatment and prophylaxis gain importance, HIV-testing and condom promotion remain essential to encourage HIV-PB. Disclosure: No significant relationships.